2008
DOI: 10.1097/ccm.0b013e318186b74e
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of fluid responsiveness in acute respiratory distress syndrome patients ventilated with low tidal volume and high positive end-expiratory pressure*

Abstract: These data show that adenoviral mediated expression of angiopoietin-1 can protect against the development of lung capillary protein leak and decrease the mortality induced by endotoxin. However, the timing of AdAng1 administration in relation to the onset of lung injury may be critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 37 publications
7
82
2
6
Order By: Relevance
“…Dynamic indices had better AUROC and correlation than static measures across studies. Furthermore, in addition to [12] Prospective observational study 2b 13 Feissel et al 2005 [13] Prospective observational study 2b 15 Natalini st al 2006 [14] Prospective observational study 2b 16 Solus-Biguenet et al 2006 [15] Prospective observational study 2b 15 Cannesson et al 2006 [16] Prospective observational study 2b 15 Lamia et al 2007 [17] Prospective observational study 2b 14 Soubrier et al 2007 [18] Prospective observational study 2b 15 Belloni et al 2008 [19] Prospective observational study 2b 16 Cannesson et al 2008 [20] Prospective observational study 2b 15 Auler et al 2008 [21] Prospective observational study 2b 14 Huang et al 2008 [22] Prospective observational study 2b 13 Biais et al 2008 [23] Prospective observational study 2b 13 Keller et al 2008 [24] Prospective observational study 2b 12 Mutoh et al 2009 [25] Randomised non-blinded study 2b 13 Ranucci et al 2009 [26] Prospective observational study 2b 15 Gouvea et al 2009 [27] Prospective observational study 2b 15 Cannesson et al 2009 [28] Prospective observational study 2b 15 Biais et al 2009 [29] Prospective observational study 2b 15 Skulec et al 2009 [30] Randomised blinded study 2b 16 Preau et al 2010 [31] Prospective observational study 2b 15 Delerme et al 2010 [32] Prospective observational study 2b 15 Desgranges et al 2011 [33] Prospective observational study 2b 14 Guinot et al 2011 [34] Prospective observational study 2b 15 Muller et al 2011 [35] Prospective observational study 2b 14 Muller et al 2012 [36] Prospective observational study 2b 15 de Oliveira-Costa et al 2012 [37] Cross-sectional observational study 2b 14 Feissel et al 2013 [38] Prospective observational study 2b 14 Brun et al 2013 [39] Prospective observational study 2b 15 Chin et al 2013 [40] Prospective observational study 2b 15 Wu et al 2014 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic indices had better AUROC and correlation than static measures across studies. Furthermore, in addition to [12] Prospective observational study 2b 13 Feissel et al 2005 [13] Prospective observational study 2b 15 Natalini st al 2006 [14] Prospective observational study 2b 16 Solus-Biguenet et al 2006 [15] Prospective observational study 2b 15 Cannesson et al 2006 [16] Prospective observational study 2b 15 Lamia et al 2007 [17] Prospective observational study 2b 14 Soubrier et al 2007 [18] Prospective observational study 2b 15 Belloni et al 2008 [19] Prospective observational study 2b 16 Cannesson et al 2008 [20] Prospective observational study 2b 15 Auler et al 2008 [21] Prospective observational study 2b 14 Huang et al 2008 [22] Prospective observational study 2b 13 Biais et al 2008 [23] Prospective observational study 2b 13 Keller et al 2008 [24] Prospective observational study 2b 12 Mutoh et al 2009 [25] Randomised non-blinded study 2b 13 Ranucci et al 2009 [26] Prospective observational study 2b 15 Gouvea et al 2009 [27] Prospective observational study 2b 15 Cannesson et al 2009 [28] Prospective observational study 2b 15 Biais et al 2009 [29] Prospective observational study 2b 15 Skulec et al 2009 [30] Randomised blinded study 2b 16 Preau et al 2010 [31] Prospective observational study 2b 15 Delerme et al 2010 [32] Prospective observational study 2b 15 Desgranges et al 2011 [33] Prospective observational study 2b 14 Guinot et al 2011 [34] Prospective observational study 2b 15 Muller et al 2011 [35] Prospective observational study 2b 14 Muller et al 2012 [36] Prospective observational study 2b 15 de Oliveira-Costa et al 2012 [37] Cross-sectional observational study 2b 14 Feissel et al 2013 [38] Prospective observational study 2b 14 Brun et al 2013 [39] Prospective observational study 2b 15 Chin et al 2013 [40] Prospective observational study 2b 15 Wu et al 2014 …”
Section: Discussionmentioning
confidence: 99%
“…Fluid responsiveness was defined as a change in cardiac output, cardiac index, stroke volume or stroke volume index of ≥ 10-20%, as measured with the bolus thermodilution technique. Pulmonary artery catheter-derived indices were compared with indices measured by LiDCO TM plus (LiDCO Ltd, London, UK) [19], automated pulse pressure variation (Intellivue MP70; Philips Medical Systems, Suresnes, France) [20]; PiCCOPlus [22,25]; transoesophageal echocardiography [26]; Phillips Intellivue (Intellivue MP70, Philips Medical Systems) [24,28,37] infrared photoplethysmography using the Finapres TM (Ohmeda Monitoring Systems, Englewood, CO, USA) [15]; and the Flotrac/ Vigileo TM (Edwards Lifesciences, Irvine, CA, USA) [28,29] (Table 3).…”
Section: Pulmonary Artery Cathetermentioning
confidence: 99%
“…Relying on pulmonary capillary wedge pressure to reflect ventricular volume, Perel et al [ 12 ] and Szold et al [15] showed that pulmonary capillary wedge pressure was related to SPV with both volume loading and phlebotomy in mechanically ventilated dogs. However, filling pressure cannot be used to reflect preload during mechanical ventilation (as is clear in Figure 4) or predict volume responsiveness [31][32][33][34]. Indeed, Denault et al [35] found that changes in systolic arterial pressure reflected changes in airway and intrathoracic pressure better than changes in echocardiographic enddiastolic area measurements in cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…연속적 자동 맥압변이의 안전성 및 유효성 평가에 선택된 문헌은 총 20편으로 연구유형은 모두 진단법 평가연구였다 (Table 3) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. [정리: 편집위원회]…”
Section: 체계적 문헌고찰 및 메타분석 결과unclassified